Chocolate Flavor Factors: From Cacao to Chocolate - Yin, Zixuan (Transactions on Environment, Energy and Earth Sciences, 2024)
Chocolate is a rich food popular all over the world. At present, there is much research on the rheological influence and chemical composition of chocolate, as well as some research on the flavor compounds of chocolate. Their main purpose is to study the effect of chocolate and the change of the composition to make chocolate healthier. However, few studies focused on the summary and comparison of chocolate flavor optimization. In this paper, the production process of chocolate and the horizontal comparison of each process are comprehensively described, and the research on flavor compounds in chocolate is analyzed. The difference in flavor compounds in different kinds of chocolate and the results of four aspects affecting the flavor of chocolate are obtained. This study makes up for the comparison between different kinds of chocolate production processes and summarizes the composition of chocolate flavor compounds and the influencing factors of chocolate flavor, which provides a reference for future related research. However, there are still some problems that cannot be solved, such as the content change of certain flavor compounds under certain processing conditions, to realize the control of chocolate flavor. Future research can also focus on the influence of human senses on chocolate flavor tasting and the improvement methods.